PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PT PEGADAIAN (PERSERO) CP TERANDAM PADANG - Aminar Sutra Dewi; Wirma Chentya (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of motivation and discipline on employee performance with job satisfaction as an intervening variable at PT Pegadaian (Persero) CP Terandam Padang. This type of research is quantitative research. The sample consisted of 87 employees of PT Pegadaian (Persero) CP Terandam Padang using total sampling. Analysis of the data used is multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that variable Motivation, discipline and job satisfaction had a positive and significant effect on employee performance at PT Pegadaian (Perssero) CP Terandam Padang. Motivation and Discipline partially have a positive and significant effect on Job Satisfaction at PT Pegadaian (Perssero) CP Terandam Padang. And job satisfaction as an intervening variable can mediate the relationship between motivation and discipline variables on employee performance